Association of ambient air pollution exposure with psychological distress in mid and later adulthood: A 26-year prospective cohort study - Thomas Canning; Marcus Richards; Anna L. Hansell; John Gulliver; Rebecca Hardy; Jorge Arias-de la Torre; Stephani L. Hatch; Ian S. Mudway; Amal R. Khanolkar; Helen L. Fisher; Ioannis Bakolis (PLoS ONE, 2025)
Background Existing evidence on associations between exposure to air pollution and psychological distress from middle to older age is limited by consideration of short exposure periods, poor historical covariates, exposures and outcomes, and cross-sectional study designs. We aimed to examine this association over a 26-year period between ages 43 and 69. Methods We utilised data from the Medical Research Council National Survey of Health and Development Study (the 1946 British birth cohort). Land-use regression models estimated exposure to specific air pollutants using household addresses for 1991 (NO2), 2001 (PM10, NO2), and 2010 (NO2, NOx, PM10, PM2.5, PMcoarse, PM2.5abs). These were linked to the closest data collection wave at ages 43, 53 and 60-64, respectively. Psychological distress was assessed through the 28-item version of the General Health Questionnaire (GHQ-28), at ages 53, 60-64 and 69. Associations between each of the pollutants with psychological distress were analysed using generalised linear mixed models, adjusted for pollution exposure before age 43, assigned sex, social class, smoking status, neighbourhood deprivation, and previous mental health problems. We also examined effect modification by social class. Results At age 69, 2125 participants completed the GHQ-28. In fully adjusted models, higher NO2 exposure was associated with higher GHQ-28 scores across a 26-year period (β=0.023, 95%CI:0.005, 0.040 per interquartile range increase in exposure), whereas higher exposure to PM10 was associated with lower GHQ-28 scores across a 16-year period (β=-0.021, 95%CI:-0.037, -0.006). There was no evidence of associations between exposure to other pollutants at age 60-64 and GHQ-28 at age 69. We found no effect modification by social class. Conclusions In this cohort there was some evidence of an association between higher cumulative exposure to NO2 and higher psychological distress, but mixed associations with other exposures. Policies to reduce pollutant exposure may help improve psychological symptoms in middle to late adulthood.